Vibration of a steam turbo-generator (TG) set during shutdown period. (August 2016) - Sinha, Jyoti K.; Hahn, W.; Elbhbah, K.; Obi-Mgbam, Kelechi G.
Highlights: Vibration behaviour of turbo-generator (TG) set during off-load shutdown condition. Last stage low pressure steam turbine blades vibration. Fatigue tests to understand the blade crack propagation even at low excitation loads. Abstract: The steam turbo-generator (TG) sets in power plants during the shutdown period often operate at a very low speed with the aid of barring gear. This low speed is known as the barring speed and it is of the order upto 100 RPM. The purpose is to float the rotor in the fluid bearings so that the rotor heavy self-weight should not cause any damage to the bearings. The barring speed also maintains uniformity of temperature across the complete rotor when cooling down from operating condition to normal condition. Operating at the barring speed is often considered as the machine is close to the stand still condition and may not be subjected to any harsh vibration problem. However the in-situ vibration measurement on a typical steam TG set during machine shutdown operating at the barring speed reveals that the machine is subjected to vibration which may have potential to propagate the existing damage further. The paper presents a typical industrial case study and observations.